Effects of Photo-Depicted Pupil Diameter on Judgments of Others' Attentiveness and on Facial Recognition Memory. Issue 2 (April 2017) - Watier, Nicholas; Healy, Christopher; Armstrong, Heather
Occasionally, individuals perceive that someone is no longer paying attention to the discussion at hand even when there are no overt cues of inattentiveness. As a preliminary study of this phenomenon, we examined whether pupil diameter might be implicitly used to infer others' attentiveness. Forty participants (27 women, 13 men, M age = 19.7 year, SD =  2.8) were presented with images of male faces with either large or small pupils, and, in the context of a personnel selection scenario, participants then judged the attentiveness of the person in the image. Images of faces with large pupils were judged as more attentive, compared with images of faces with small pupils. Face recognition memory performance was not affected by depicted pupil size. Our results are consistent with the proposal that pupillary fluctuations can be an index of perceived attention, and they provide preliminary evidence that pupil dilation may be implicitly relied upon to infer attentional states.